Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk - Alberto Berardi; Chryssoula Tzialla; Laura Travan; Jenny Bua; Daniele Santori; Milena Azzalli; Caterina Spada; Laura Lucaccioni; on behalf of the GBS Prevention Working Group of Emilia-Romagna (BMC, 2018)
Abstract Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.